Simple Whole-Mount Staining Protocol of F-Actin for Studies of the Female Gametophyte in Agavoideae and Other Crassinucellate Ovules - González-Gutiérrez, Alejandra G.; Verdín, Jorge; Rodríguez-Garay, Benjamín (Frontiers in Plant Science, 2020)
During plant sexual reproduction, F-actin takes part in the elongation of the pollen tube and the movement of sperm cells along with it. Moreover, F-actin is involved in the transport of sperm cells throughout the embryo sac when double fertilization occurs. Different techniques for analysis of F-actin in plant cells have been developed: from classical actin-immunolocalization in fixed tissues to genetically tagged actin with fluorescent proteins for live imaging of cells. Despite the implementation of live cell imaging tools, fixed plant tissue methods for cytoskeletal studies remain an essential tool for genetically intractable systems. Also, most of the work on live imaging of the cytoskeleton has been conducted on cells located on the plant’s surface, such as epidermal cells, trichomes, and root hairs. In cells situated in the plant’s interior, especially those from plant species with thicker organ systems, it is necessary to utilize conventional sectioning and permeabilization methods to allow the label access to the cytoskeleton. Studies about the role of F-actin cytoskeleton during double fertilization in plants with crassinucellate ovules (e.g., Agave, Yucca, Polianthes, Prochnyantes, and Manfreda) remain scarce due to the difficulties to access the female gametophyte. Here, we have developed a straightforward method for analysis of F-actin in the female gametophyte of different Agavoideae sub-family species. The procedure includes the fixation of whole ovules with formaldehyde, followed by membrane permeabilization with cold acetone, a prolonged staining step with rhodamine-phalloidin, and Hoechst 33342 as a counterstain and two final steps of dehydration of samples in increasing-concentration series of cold isopropanol and clarification of tissues with methyl salicylate. This technique allows the analysis of a large number of samples in a short period, cell positioning relative to neighbor cells is maintained, and, with the help of a confocal microscope, reconstruction of a single 3D image of F-actin structures into the embryo sac can be obtained.